2005
DOI: 10.1128/iai.73.9.5645-5653.2005
|View full text |Cite
|
Sign up to set email alerts
|

Early Cytokine Production Is Associated with Protection from Murine Cerebral Malaria

Abstract: Cerebral malaria (CM) is an infrequent but serious complication of Plasmodium falciparum infection in humans. Animal and human studies suggest that the pathogenesis of CM is immune mediated, but the precise mechanisms leading to cerebral pathology are unclear. In mice, infection with Plasmodium berghei ANKA results in CM on day 6 postinoculation (p.i.), while infection with the closely related strain P. berghei K173 does not result in CM. Infection with P. berghei K173 was associated with increased plasma gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 50 publications
(47 reference statements)
10
99
0
2
Order By: Relevance
“…Specifically, we observed no significant differences in the T-cell response to PyL or PyNL, and despite differences in the kinetics of the IFN-␥ and NK responses to each of the two parasite strains, we found that the course of acute infection was essentially unaffected by the absence of T or B lymphocytes, NK cells, or IFN-␥. These data are somewhat unexpected, given the important roles that IFN-␥-producing NK cells and T lymphocytes play in other rodent malaria infections, such as P. berghei ANKA and P. chabaudi chabaudi (28,30,51), and highlight significant differences in the mechanisms of control of P. yoelii compared with other malaria infections. In contrast, depletion of macrophages with clodronate liposomes markedly reduced the ability of the mice to control acute PyL or PyNL infection.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Specifically, we observed no significant differences in the T-cell response to PyL or PyNL, and despite differences in the kinetics of the IFN-␥ and NK responses to each of the two parasite strains, we found that the course of acute infection was essentially unaffected by the absence of T or B lymphocytes, NK cells, or IFN-␥. These data are somewhat unexpected, given the important roles that IFN-␥-producing NK cells and T lymphocytes play in other rodent malaria infections, such as P. berghei ANKA and P. chabaudi chabaudi (28,30,51), and highlight significant differences in the mechanisms of control of P. yoelii compared with other malaria infections. In contrast, depletion of macrophages with clodronate liposomes markedly reduced the ability of the mice to control acute PyL or PyNL infection.…”
Section: Discussionmentioning
confidence: 70%
“…7C and D). However, given the essential role of IFN-␥ in controlling nonlethal P. chabaudi infection (28,31,51,56) and in preventing cerebral malaria in P. berghei K173 infection (30), it was rather unexpected to find that during PyNL infection, the course of infection was essentially identical in WT and IFN-␥ Ϫ/Ϫ mice (Fig. 7B, C, and D).…”
Section: Vol 75 2007 Control Of Lethal and Nonlethal P Yoelii Infementioning
confidence: 91%
See 1 more Smart Citation
“…38 -41 The inoculum number was greater for PbK because this prevents the occurrence of CM in C57BL/6 mice. 39 Age-matched BALB/c mice, housed under similar conditions, received 10 6 PbA-infected erythrocytes and served as another non-CM control group. Comparisons were made on days 7 and 8 after infection, at which time peripheral parasitemia was similarly low (mean, 4.8% to 10.4%) in all groups, thereby ruling out any confounding factors caused by global hypoxia secondary to anemia.…”
Section: Mice Parasites and Infectionmentioning
confidence: 99%
“…Mice injected with PbK-parasitized RBCs develop high parasitemia and severe anemia and die without cerebral symptoms 18-22 days post-infection. 31 We then infected Erfedeficient mice and examined the impact of Erfe deletion on hepcidin expression, parasitemia and RBC indices. By highlighting the contribution of ERFE in hepcidin regulation in malaria, this study may suggest new therapeutic strategies to combat malaria.…”
Section: Erythroferrone Contributes To Hepcidin Repression In a Mousementioning
confidence: 99%